Clinical profile of a cohort of neonates with seizures: Association between semiology, etiology, and electroencephalographic findings - Natália Corrêa de Corrêa; Julia Machado da Silveira Bom; Monique Ribas Scherer; Magda Lahorgue Nunes (Elsevier, 2022)
Background: Seizures are the most common sign of neurologic dysfunction, reflecting a wide variety of central nervous system disorders. Methods: A retrospective cross-sectional study of neonates with a clinical diagnosis of seizures was conducted in order to verify relationships between clinical aspects and EEG findings. Patients were divided into 3 groups according to the EEG recording available as: 1) with confirmatory ictal EEG; 2) with altered but non-ictal EEG; and 3) without any EEG recording. Variables related to pregnancy and birth history, neonatal complications, and seizure semiology (by video or clinical description) were compared to EEG findings. Results: 97 neonates were included (39.1% preterm, 54.6% male), 71 with available EEG data (56.3% with ictal EEG). The group without EEG presented clinical characteristics significantly different from the others such as extreme prematurity, low birth weight, and higher neonatal mortality (P = 0.002, 0.001, and 0.003, respectively). The most common etiology was hypoxic-ischemic encephalopathy (HIE) (46.4%) followed by vascular disorders, which predominated in extremely preterm neonates (P = 0.006). Sequential seizure was the most common type (44.6%) and was more frequently identified in term neonates (46%). In 51.2% of the ictal recordings the main finding was electrographic seizure without clinical manifestation. Discharge using antiseizure medication was higher among those with ictal or altered non-ictal EEG (P < 0.001). Conclusions: HIE is still a frequently etiology for neonatal seizures. Even if the patients in the sample were not under continuous EEG, the substantial proportion of electrographic seizures without clinical manifestations detected suggests the importance of continuous EEG monitoring in neonates at increased risk of seizures.